Politik Hukum Pengaturan Unsur Pimpinan Partai Politik - Kuswanto (Perspektif Hukum, 2016)
Political party is a precondition for democracy. Political party should receive public trust to exist as the people’s representative. Indonesian politics today distrusts the political party. Because of commiting criminal offense such as corruption, many politicians are prosecuted. To respond this situasion, the dignity of the political party needs to be restored. This article recommends that requirements of political party leader should be regulated in legislation. Political party leader should have moral and ethics capability higher than its regular member. Furthermore, this article also recommends that the Law Number 2 of 2008 should be amended to accommodate this research finding.